Two-Period Financial Contracts with Private Information and Costly State Verification - Webb, D. C. (Quarterly Journal of Economics, 1992)
Journal Article Two-Period Financial Contracts with Private Information and Costly State Verification Get access David C. Webb David C. Webb London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 107, Issue 3, August 1992, Pages 1113–1123, https://doi.org/10.2307/2118378 Published: 01 August 1992